Reconstructing the fragmented slave mother – the mind, body and spirit in beloved. - Fwah, Benjamin Zhengwei. (2013)
This paper seeks to prove that the past, present and future of Sethe’s life bears a corresponding relationship with her mind, body and spirit respectively. Slavery has caused Sethe to be placed in a paradoxical situation of being both a mother and a slave. She becomes fragmented and entrapped by trauma from the past, unable to live her life to the fullest. By establishing that spirituality involves an awareness of the entrapping nature of trauma and reclaiming ownership of one’s life, I will seek to show how it leads to healing. This paper would focus on how slavery still lingers on in the past and present for Sethe, evident in the trauma of the mind and bodily scars on her body respectively, reshaping her into a broken figure, but spirituality allows Sethe to reassert her own life in order to construct a better future for herself. Thus in my exploration of slave motherhood, specifically in Beloved, I will draw the connection that Sethe’s traumatic past as a slave has caused her to be shaped into a broken mother figure bearing the horrific scars in the present, but her spirit allows her to recognise the ill-effects of being entrapped, enabling her to take action to banish her demons and reassert her own future.